Did Gurdjieff Write Scripture?. Issue 2 (1st February 2022) - Azize, Joseph
Abstract : Did Gurdjieff write scripture? Can we understand Gurdjieff's writings in terms of a category he did not use? Conversely, can Gurdjieff's ideas and practices be used to understand scripture in other traditions? For Gurdjieff, the important lens of scrutiny was not "scripture" but his own categories of "objective art" and "subjective art." He considered at least some of his writings to be objective art, constructed in accordance with cosmic laws. For him, the being-state (the total condition) of both the writer and the reader or listener, was as important as the ideas imbibed, for delivery and reception are in dynamic relation. Finally, the controversy surrounding the revision of his First Series, published in 1992 and retranslated by 2006, is examined. The evidence suggests that while Gurdjieff did contemplate that typographical and minor errors might be corrected, he would have deprecated the full-scale revision of the entire English text which was undertaken, as substituting "subjective" for "objective" art.